تطوير الموسوعة السياحية على أساس الصورة الفوتوغرافية في الوكالة السياحية لمدينة مالانج - Ahmad Alfian (Abjadia, 2017)
إن قلة الأخبار عن الأماكن السياحية بمدينة مالانج تجعلها غير شهيرة ونادرة في زيارة، فهي تحتاج إلى الوسائل المذيرة والجاذبة ليتجذب إليها السياحيون حيث أن تلك الوسائل تحتوي على الأخبار المهمة للتعرف بالتفصيل على تلك الأماكن السياحية. والفكرة الأساسية لهذا الدليل الكتابي هي كونها الكتاب الذي يحتوي على لحمة قصيرة وبيان مهم عن بعض الأماكن السياحية البحرية بمدينة مالانج. وتعرف تلك الأماكن السياحية يحتاج إلى عرض بعض صور تتعلق بها، وكذا إخبار بعض بيانات مهمة كالخريطة السياحية، وبيانات السكن، وبيانات المواصلات، وكل ما يحتاج إليه السياحيون. ومنهج هذا البحث هو البحث والتطوير (Research and Development) في تكييف برغ وغال (Borg Gall) بالمدخل الكيفي لتحليل البيانات من الملاحظة والاستبيانات إلى السياح والخبير وتحليل مضمون الوثائق والمقابلة. نتائج هذا البحث كما يلي: 1) يتم تطوير الموسوعة السياحية على أساس الصورة الفوتوغرافية،بخطوات البحث والتطوير عند برغ وغال (Borg and Gall) وفيه يتكون من 25موضوعا 2) صلاحية هذا التطبيق من تحكيم خبير المادة حصل على 75٪ بمعيار جيد، والحاصل من خبير التصميم حصل على 85,52٪ بمعيار جيد جدا. 3) وفعاليته في التجربة المبدئية تحتوى على 10 سياحا حصل على 65,75٪ بمعيار متوسط والتجربة الميدانية تحتوى على 10 سياحا حصل على 75,83٪ بمعيار ممتازThe lack of information makes the tourist spots in Malang is little known and rarely visited. For that, we need a media that appeals to tourists that contains a lot of information that is important so that in addition to providing information but also can help to introduce the tourist attractions. The concept of the design of this manual is a book that contains some where nautical tourism is in Malang. To perform an introduction to tourist spots done by unleashing some pictures of the place, and also provide additional information such as tourist maps, information about accommodation and transportation and also the needs of prospective travelers before heading tourist attractions. While the research method used in this research is research and development method (R D) by adapting the method by Borg and Gall with using a qualitative approach to analyze the results obtained from observation, questionnaires test to students and experts, archival document and interview. The results of this study are as follows: 1) Make development of  Travel  Encyclopedia based on photographic illustration in by steps Borg Gall research and development and which contains nine Nahwu subject. 2) The percentage of validation test by content experts is up to 75% which is at a good criteria, and the percentage of validation test by design experts is up to 85.52% which is at a very good criteria. 3) Besides that, the researcher also conducts a field test in two phases, the limited test to 10 travelers that reach the percentage up to 65,75% which is at a good criteria and field test to 10 travelers that reach the percentage up to 75,83% which is at a very good criteria.